Muguras sāpes ārstniecības personām un to biežākie rašanās iemesli ambulatorajā praksē - Borģe, Iveta (Latvijas Universitāte, 2017)
Bakalaura darba tēma ir „Muguras sāpes ārstniecības personām un to biežākie rašanās iemesli ambulatorajā praksē”. Autore ir izpētījusi muguras sāpju rašanās iemeslus un to specifiku ārstniecības personām ambulatorajā praksē. Bakalaura darba pirmajā nodaļā autore ir teorētiski analizējusi muguras sāpju būtību, veidus un to rašanās specifiku ārstniecības personām ambulatorajā praksē. Otrajā nodaļā autore raksturojusi muguras sāpes un to rašanās iemeslus veselības aprūpē strādājošo arodslimību kontekstā. Trešajā nodaļā ir izpētīts muguras sāpju biežumu un to rašanās cēloņi ārstniecības personām ambulatorajā praksē. Bakalaura darba noslēgumā autore ir apkopojusi iegūtos rezultātus un izdarījusi secinājumus, kā arī izstrādājusi preventīvo pasākumu kopumu ārstniecības personām muguras sāpju novēršanai. Izstrādājot darbu autore izmantoja kvantitatīvo pētniecības metode- aptauju, kā arī statistiskās metodes- pētījuma datu apkopošana, sistematizēšana un grafiska atspoguļošana Atbildot uz pētījuma jautājumu: Vai pastāv atšķirības muguras sāpju biežumā un to rašanās iemeslos starp ārstniecības personām ambulatorajā praksē?- autore secina, ka Nepastāv būtiska atšķirība starp ārstu, ārsta palīgu un ambulatorās māsas muguras sāpju cēloņiem, to veicinošiem un ietekmējošiem faktoriem un informācijas iegūšanas avotiem par muguras sāpju iemesliem.

The subject of the Bachelor' s paper is " Bad Back in Medical Personnel and its most Common Causes in Ambulatory Practice". The Author has investigated causes of back pain and its specifics amongst medical personnel in ambulatory practice. In the First Chapter of the work, the Author has analysed theoretically the essence, varieties and causes specifics of the back pain in medical personnell at ambulatory practice. In the Second Chapter, the Author has characterised the back pain and its origins in the context of occupational disease of health care workers. Frequency and causes of the back pain in the medical personnel in ambulatory practice are researched in the Third Chapter. In the Conclusion of her Bachelor' s paper, the Author has summarised the results of the investigation and described outcomes. She has also elaborated complex of preventive enterprises for medical personnel to avoid the back pain . In the paper, the Author has used the quantitative research method- survey, as well as statistical methods- research data summarising, systematization and graphic reflection. In response to the main research question: Are there differences in frequency and causes of the back pain amongst medical personnel in ambulatory practice?- the Author concludes that there are no essential differences amongst causes, their benefitting and influencing factors and information sources on causes of the back pain amongst positions of Doctors, Doctoral Assistants and Nurses. The subject of the Bachelor' s paper is " Bad Back in Medical Personnel and its most Common Causes in Ambulatory Practice". The Author has investigated causes of back pain and its specifics amongst medical personnel in ambulatory practice. In the First Chapter of the work, the Author has analysed theoretically the essence, varieties and causes specifics of the back pain in medical personnell at ambulatory practice. In the Second Chapter, the Author has characterised the back pain and its origins in the context of occupational disease of health care workers. Frequency and causes of the back pain in the medical personnel in ambulatory practice are researched in the Third Chapter. In the Conclusion of her Bachelor' s paper, the Author has summarised the results of the investigation and described outcomes. She has also elaborated complex of preventive enterprises for medical personnel to avoid the back pain . In the paper, the Author has used the quantitative research method- survey, as well as statistical methods- research data summarising, systematization and graphic reflection. In response to the main research question: Are there differences in frequency and causes of the back pain amongst medical personnel in ambulatory practice?- the Author concludes that there are no essential differences amongst causes, their benefitting and influencing factors and information sources on causes of the back pain amongst positions of Doctors, Doctoral
Bad Back in Medical Personnel and its Most Common Causes in Ambulatory Practice
Keywords: Medicīna; muguras sāpes; ārstniecibas personas ambulatorajā praksē; preventīvie pasākumi; muguras sapju profilakse